Computed tomographic angiography in intracranial vascular diseases - Miloševič, Zoran (Radiology and oncology (Ljubljana), 2000)
Background. The development of spiral computed tomography (CT) introduced a more precise imaging of the vessels also with computed tomographic angiography(CTA). Because it is a minimaly invasive method, it was widely accepted by radiologists and clinicians. In early 90ties CTA also accompanied conventional angiography and magnetic resonance angiography (MRA) in imaging of intracranial vascular diseases. CTA is used for the detection and evaluation of intracranial aneurysms, vascular malformations, stenoocclusive diseases of intracranial arteries and pathological changes of venous sinuses. Comparing to conventional angiography as the "gold standard", CTA has high specificity, sensibility and diagnostic accuracy concerning detections of intracranial aneurysms. Regarding vascular malformations, CTA is used for diagnostics and pre and postopeative evaluation of it. CTA can show good results in imaging of venous angiomas, and so invasive conventional angiography can be avoided in this pathology. Stenosis and occlusions of arteries can be diagnosed and evaluated in patients with cerebral vasospasm, patients with acute stroke, and patients with chronical arterial stenoses and occlusions. CTA is useful for the demonstration of occusive and stenosing changes of intracranial venous sinuses. Conclusion. With CTA it is possible togenerate threedimensional reconstructed images which give a more accurate determination of anatomical relations in intracranial vascular diseases. The main disadventage of CTA in comparison to intraarterial angiography is the lower spatial resolution of CTA, but is constantly imprving with the development of better scanners and workstations, so that there are great possibilities for further deveopement and wider use of CTA in the diagnosis ofintracranial vascaular diseases.
Keywords: angiografija; Arterial occlusive diseases; Cerebral aneurysm; Cerebral angiography; Cerebral arteriovenous malformations; Cerebral ischemia, transient; Cerebrovascular disorders; diagnostika; Hemangioma; ožilje; Sensitivity and specificity; Sinus thrombosis; Tomography, X-ray computed; žilne bolezni